The clinician safety culture and leadership questionnaire: refinement and validation in Australian public hospitals. (3rd December 2019) - Clay-Williams, Robyn; Taylor, Natalie; Ting, Hsuen P; Winata, Teresa; Arnolda, Gaston; Braithwaite, Jeffrey
Abstract: Objective: This study aimed to refine and validate a tool to measure safety culture and leadership in Australian hospitals. Design: The clinician safety culture and leadership questionnaire was constructed by combining and refining the following two previously validated scales: Safety Attitudes Questionnaire and the Leadership Effectiveness Survey. Statistical processes were used to explore the factor structure, reliability, validity and descriptive statistics of the new instrument. Setting: Thirty-two large Australian public hospitals. Participants: 1382 clinicians (doctors, nurses and allied health professionals). Main Outcome Measure(s): Descriptive statistics, structure and validity of clinician safety culture and leadership scale. Results: We received 1334 valid responses from participants. The distribution of ratings was left-skewed, with a small ceiling effect, meaning that scores were clustered toward the high end of the scale. Using confirmatory factor analysis, we confirmed the structure of the three scales as a combined measure of safety culture and leadership. The data were divided into equal calibration and validation datasets. For the calibration dataset, the Chi-square: df ratio was 4.4, the root mean square error of approximation RMSEA (a measure of spread of the data) was 0.071, the standardized root mean square residual SRMR (an absolute measure of the fit of the data) was 0.058 and the Confirmatory Fit Index (CFI) (another test confirming the fit of the data) was 0.82; while none of the indices suggested good fit, all but CFI fell within acceptable thresholds. All factors demonstrated adequate internal consistency and construct reliability, as desired. All three domains achieved discriminant validity through cross-loadings, meaning that the three domains were determined to be independent constructs. Results for the validation dataset were effectively identical to those found in the calibration dataset. Conclusions: While the model may benefit from additional refinement, we have validated the tool for measuring clinician safety culture and leadership in our Australian sample. The DUQuA safety culture and leadership scale can be used by Australian hospitals to assess clinician safety culture and leadership, and is readily modifiable for other health systems depending on their needs.